Early Devonian Slab Melting of the Proto-Tethys Ocean: Insights from Adakitic Granitoids in the Jiayuguan Area, Hexi Corridor (NW China) - Qigui Mao; Wenjiao Xiao; Rui Li; Songjian Ao; Dongfang Song; Miao Sang; Hao Wang; Zhou Tan (Lithosphere)
The tectonics of the Proto-Tethys Ocean during the Early Devonian are still heavily debated in the North Qilian orogen. In order to further constrain this issue, we explore geology, chronology, geochemistry, and isotopes of three newly discovered Early Devonian adakitic granitoids of the Jiayuguan complex in the North Qilian orogen, NW China. The granitoids exhibit typical adakitic geochemical signatures with high SiO2 (>56%), Na, Al, and Sr contents, depleted in Yb and Y, and high Sr/Y (82–277) and (La/Yb)N (7.65–15.16) values. Additionally, their high Mg# (62–68) and εHf(t) (+6.5–+11.9) values indicate partial melting of slab genesis. However, they have comparatively low εNd(t) (−2.3–+0.13). Their incompatible Hf and Nd isotopes could be caused by contamination between the source magma and continental crust during the emplacement processes. The three adakitic granitoids yield zircon U–Pb ages of 415–403 Ma, implying that the northern Qilian Ocean was subducting until the Early Devonian (403 Ma) and that young/hot/ridge subduction formed the Jiayuguan adakitic granitoids. Combined with regional data, we propose that the Proto-Tethys Ocean was subducting until 403 Ma in the Qilian area.